Designing a mobile-based infaq application markazul quran wassunnah foundation (MQS)Kuantan Singingi - Jasri, Jasri; Al-hafiz, Nofri Wandi (Jurnal Teknik Informatika C.I.T Medicom, 2023)
The Android-based Infaq application for the Markazul Quran Wassunnah foundation is an innovative solution to support the management and collection of infaq and donations for the Markazul Quran Wassunnah foundation efficiently and transparently. This application is designed to make it easier for users to contribute to the Markazul Quran Wassunnah foundation, as well as to enable the managers of the Markazul Quran Wassunnah foundation to better manage funding sources. The application's main features include real-time processing of infaq, alms, zakat, and notifications, ensuring that the collected infaq is used appropriately according to the objectives determined by the management of the Markazul Quran Wassunnah foundation. This application is expected to increase community participation in supporting the development of the Markazul Quran Wassunnah foundation and encourage the use of technology for religious purposes and social benefits.